PELATIHAN STORYTELLING BAGI ANGGOTA IKATAN PELAJAR PUTRI NAHDLATUL ULAMA (IPPNU) DESA KEDUNGBANTENG SEBAGAI UPAYA PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS - Yasinta Wulandari; Asfi Aniuranti; M.Happy Nur Tsani (LPPM Universitas Bina Bangsa, 2023)
Comunication ability is one of the soft skills that is supposed to be mastered by youth in this modern era. This ability can be trained by doing lots of social activities at schools or community. Organisation for youth is one of the places that can be used to improve this communication ability. Communicating in English is now becoming important in all aspects, for example, education, business, health, technologies, etc. Therefore, being able to communicate in English is needed. However, many people still think that communicating in English is difficult. One of them is IPPNU Kedungbanteng members. They still found difficulties and felt unconfident to communicate in English. Therefore, storytelling training was done because this interesting method can be used to improve confidence in communication. The participants of the training were given material related to concept of storytelling and how to prepare storytelling. The result shows that the participants gave positive responses toward the training activities and storytelling